MULTICRITERIAL OPTIMIZATION OF HIERARCHICAL STRUCTURES - Voronin , A. N. (Problems of Informatization and Management, 2021)
Complex socio-economic management systems are characterized by branched hierarchical structures, and the quality of their functioning is assessed by vector criteria [1-8]. Such systems can include the national economy as a whole, its industries, aviation and rocket-space complexes, information systems, target programs, etc. System analysis of modern large control systems increasingly uses hierarchical models, which makes the problem of their study relevant.